2007
DOI: 10.1177/021849230701500312
|View full text |Cite
|
Sign up to set email alerts
|

Endothoracic Papaverine Application for Internal Thoracic Artery Harvest

Abstract: This study compared the effects of different methods of papaverine application on free blood flow and harvesting time of the internal thoracic artery for coronary bypass grafting. Patients were randomly divided into 3 groups of 25 each: group 1 had papaverine injected into the endothoracic tissue around the internal thoracic artery before dissection, group 2 had papaverine injected into the periarterial tissues of the internal thoracic artery pedicle, and group 3 had intraluminal papaverine applied retrogradel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…3,5 Topical therapy has included covering the artery with a papaverinesoaked sponge, spraying the vessel with papaverine, and immersing the IMA in a papaverine-filled surgical glove. 1,5,6,9 Mulay et al 10 described a method of delivering papaverine to the mammary artery bed before IMA dissection, making harvest easier. IMA spasm is complex and not fully understood, but surgical dissection certainly contributes to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 Topical therapy has included covering the artery with a papaverinesoaked sponge, spraying the vessel with papaverine, and immersing the IMA in a papaverine-filled surgical glove. 1,5,6,9 Mulay et al 10 described a method of delivering papaverine to the mammary artery bed before IMA dissection, making harvest easier. IMA spasm is complex and not fully understood, but surgical dissection certainly contributes to it.…”
Section: Discussionmentioning
confidence: 99%
“…This vasodilator can be used topically and intraluminally 3,5 . Topical therapy has included covering the artery with a papaverine‐soaked sponge, spraying the vessel with papaverine, and immersing the IMA in a papaverine‐filled surgical glove 1,5,6,9 . Mulay et al 10 described a method of delivering papaverine to the mammary artery bed before IMA dissection, making harvest easier.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple techniques for papaverine delivery have been studied, such as intraluminal papaverine injection, perivascular papaverine injection, submerging of the ITAs graft in papaverine solution, papaverine injection in the endothoracic fascia, and topical papaverine spray. Studies have shown that intraluminal papaverine administration offers more benefits than other techniques, but it is associated with the risk of intimal injury [ 33 , 68 , 72 , 73 ]. A study compared the effect of papaverine administration by two different techniques, topical spray, and perivascular injection while administering the same dose to both groups.…”
Section: Different Methods Of Papaverine Deliverymentioning
confidence: 99%
“…The histopathology examination of the distal end also confirmed the intact integrity of the graft [ 32 ]. Bahcivan et al injected papaverine instead of normal saline and found that papaverine helps decrease harvesting time and avoid spasm and reuse of papaverine after harvesting [ 33 ]. Saxena et al also used papaverine for harvesting purpose.…”
Section: Hydro Dissection Technique For Itas Harvestingmentioning
confidence: 99%
“…We read with great interest the article by Bahcivan and co-workers 1 regarding their experience with the use of papaverine for improving the fl ow in internal thoracic artery (ITA) as a conduit for coronary artery bypass surgery (CABG). The authors compared three different methods of using papaverine, which included injection into endothoracic fascia, into the pedicle of ITA following harvesting and direct intraluminal injection of the drug.…”
Section: Papaverine Hydrodissection Of Internal Thoracic Arterymentioning
confidence: 99%